Determination of eight lignans in Schisandra chinensis and Schisandra sphenanthera (Bangladesh Journal of Pharmacology, 2016)
A high performance liquid chromatography method for the determination of eight lignans contents in Schisandra chinensis and Schisandra sphenanthera was developed. The chromatographic column was Agilent ZORBAX 300SB-C18 column (4.6 mm × 250 mm?5 ?m). The mobile phase was methanol-water, a gradient elution was conducted and the detection wavelength was at 230 nm. The results showed that the recovery rate of eight lignans was 92.2-102.9% and RSD was 1.5-4.2%. The established content determination method was simple, sensitive, accurate and stable, and can be used to control the quality of S. chinensis and S. sphenanthera.